ПЕДАГОГІЧНІ УМОВИ ФОРМУВАННЯ РЕФЛЕКСИВНИХ УМІНЬ СТУДЕНТІВ ПЕДУНІВЕРСИТЕТУ (Педагогіка вищої та середньої школи, 2008)
Didactic terms, coopérant forming of abilities of reflections of students of pedagogical universities, are examined in the article.